Effect of Information Systems Management and Competencies To Performance Employees Part In Dyeing: Effect of Information Systems Management and Competencies To Performance Employees Part In Dyeing - Wala Erpurini (Institute of Computer Science (IOCS), 2020)
This research was conducted in part Dyeing for their information systems are not used continuously, and not applying selection of employees in accordance with their respective competences. Resulting in a decrease employee performance such as a sense of responsibility for work that is not good. The purpose of this study was to determine the effect of management information systems, competency and performance in the dyeing department employees. The method used is descriptive method and associative, the method of research that seeks to said the settlement problem is happening now by considering past. The analysis showed that partially Management Information System significantly influence employee performance, both directly and indirectly. Competence significant effect on employee performance. Then based on the results of the path analysis, can be obtained that has the biggest contribution to performance is variable competence.